Analisis Sistem Pelayanan Penyakit Jantung di RSUD Dr. Kanujoso Djatiwibowo Balikpapan Tahun 2014 - Jais, Ahmad (UI Scholars Hub, 2018)
Decomposition Analysis System is operating a system that includes identification efforts objectives, activities, implementation of activities, the situation faced and information needed at each stage of system implementation. This study uses a blend of Systems Theory approach Donabedian-Azwar, the principal stages of Structural or Input Process-Output or Outcome to look at heart disease care system in hospitals Dr.Kanujoso Djatiwibowo Balikpapan 2014. The study was conducted from April to November 2015, using a design qualitative descriptive analytic method. Analysis was performed with the data derived from the study of medical documents cardiac patients in hospitals Dr Kanujoso Djatiwibowo Balikpapan in 2014, observation and depth interview with selected informants. The results showed a factor of structure or Inputs that influence mortality in cardiovascular disease care system in the Hospital Dr Kanujoso Djatiwibowo Balikpapan is Patient factors, human resources, facilities, and methods. Factors such as the process of service delivery, the doctor- nurse coordination and integration of services. It is recommended that the hospitals Dr Kanujosos Djatiwibowo Balikpapan perform additional doctors Heart Specialist, create one- stop service for cardiovasculardisease or Cardiac Center and increase cooperation orcoordination between the hospitals Dr Kanujosos Djatiwibowo with Primary Health Care Facility, City Health Department Balikpapan and house parties other hospitals in the city of Balikpapan.